Desain 2D Game Platform Petualangan Gajah Berbasis Android - Kharis Furqonnil Hakim; Donaya Pasha; Qadhli Jafar Adrian (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
Game is one of the activities carried out by some people to seek entertainment and fun as a reliever of boredom. Over time, the development of information and communication technology is currently growing very rapidly in various fields, one of which is the development of games. Games are not only used as entertainment, but games can also be used as learning media, business fields, and as sports. This game has several genres, namely, First Person Shooter, Fighting Game, Racing Game, Role Play Game, Multiplayer, Adventure, Simulation, Strategy, and Platform. This study aims to produce an Android-Based 2D Platform Game Design for Adventure of The Elephant. The results of this study make a game that is quite challenging and trains patience for those who play it. In its manufacture, the right system development method is needed, so that the game that will be built is as desired. The researcher uses the Game Development Life Cycle (GDLC) system development method. The results of the game feasibility test using the ISO 25010 testing method on the functional suitability aspect of 100%, on the usability aspect of 90.34%, and on the portability aspect of 100%..